POLA STRUKTUR DAN GEODINAMIKA CEKUNGAN BULA, BERDASARKAN ANOMALI GAYA BERAT - Budi Setyanta; Imam Setiadi (Pusat Survei Geologi, 2010)
Gravity is one of the geophysical methods that can be used to estimate subsurface condition based on the density of rocks. Seram bouguer anomaly map reduced by density 2.67 gr/cc indicates negative anomaly pattern in Bula Basin with anomaly range between ( -50 mgal – 0 mgal). Gravity data analyses were carried out by separating the residual and regional anomalies using moving average filtering and second vertical derivative. The subsurface modeling was done by using gravmag forward modeling software. The results show two regional faults i.e. the norteast-sothwest strike slip fault and the east-west thrust fault. Those faults have different periods. The filtering using moving average and second vertical derivative shows closure areas and fold within Pretertiary rocks that geologically are interesting features.Keywords : Gravity, moving average, second vertical derivative, Bula Basin